IMPLIKASI HUKUM PEMBATALAN PUTUSAN BADAN ARBITRASE NASIONAL YANG BELUM TERDAFTAR PADA PENGADILAN NEGERI - Arga Febrian; Lanini, Agus; Fadjar, Adfiyanti (TADULAKO MASTER LAW JOURNAL, 2024)
This writing aims to analyze the legal implications of filing an annulment of a decision by a national arbitration body that has not been registered with the District Court where the respondent lives (case study of Tolitoli District Court decision number 23/Pdt.G/2021/PN.Tli). This writing uses normative juridical research methods in analyzing the problems that arise in this research. That the nature of the arbitration body's decision is final and binding so that there is no legal remedy if the losing party is not satisfied with the arbitration decision. However, in Law Number 30 of 1999 concerning arbitration and alternative settlement solutions, if the arbitration award in the process turns out to contain evidence that was hidden but not presented at trial, there is a misunderstanding about the agreement being entered into, and there is deception, then the arbitration award can still be annulled at District Court where the arbitration respondent is domiciled. However, in practice there are still arbitration awards that are registered that do not comply with the provisions of the Arbitration Law, so that the legal status of arbitration awards that are requested to be annulled is unclear. In this article, we will discuss the legal meaning of an arbitration award that is requested to be annulled but has not been registered in the District Court, as well as finding a solution if an arbitration award has not been registered in the District Court but has been requested to be annulled by the District Court. Penulisan ini bertujuan untuk menganalisis implikasi hukum pengajuan pembatalan putusan badan arbitrase nasional yang belum didaftarkan di Pengadilan Negeri tempat tinggal termohon (studi kasus putusan Pengadilan Negeri tolitoli nomor 23/Pdt.G/2021/PN.Tli). Penulisan ini menggunakan metode penelitian yuridis normatif dalam menganalisis permasalahan yang timbul dalam penelitian ini. Bahwa sifat putusan badan arbitrase bersifat final and binding sehingga tidak terdapat upaya hukum apabila pihak yang kalah tidak merasa puas terhadap putusan arbitrase. Namun didalam Undang-Undang Nomor 30 Tahun 1999 tentang arbitrase dan alternatif penyelesaian sengketa, jika putusan arbitrase dalam prosesnya ternyata terdapat bukti yang disembunyikan namun tidak dihadirkan dipersidangan, terdapat kesalahpahaman tentang perjanjian yang diperjanjikan, dan terdapat tipu muslihat , maka putusan arbitrase masih dapat dibatalkan pada Pengadilan Negeri tempat termohon arbitrase berdomisili. Namun dalam prakteknya masih terdapat putusan arbitrase didaftarkan tidak sesuai dengan ketentuan UU Arbitrase, sehingga putusan arbitrase yang hendak dimohonkan untuk dibatalkan tidak jelas status hukumnya. Olehnya dalam penulisan ini akan dibahas implikasi hukum atas putusan arbitrase yang dimohonkan dibatalkan namun belum terdaftar diPengadilan Negeri, serta untuk mencari solusi bilamana putusan arbitrase belum terdaftar pada Pengadilan Negeri namun telah dimohonkan untuk dibatalkan oleh Pengadilan Negeri.